Кодекс «іншого світу» і проблема неморального героя в казках - Радулович, Н. (Народна творчість та етнологія, 2012)
The attempts to comprehend the moral code of fairy tales are mostly oriented toward the world of human beings. Yet, the creatures «from another world» (demonic creatures, witches) have their own code, which differs from the human one by emphasizing cannibalism, cruelty, and physical strength, which shows that it is more archaic. Making a distinction between human and nonhuman code we can explain the so-called «immoral» behavior of the hero, because he behaves so towards his adversaries from the «another world», on whom usual code cannot be applied.